Our Stories: A Woman, A Teenager, A Single Mother: Psychological Well-being of a Single Mother Adolescents - Anggi Tessalonika Lena; Yeni Damayanti; Juliana Marlin Y. Benu (Journal of Health and Behavioral Science, 2021)
The purpose of this study was to determine the psychological well-being of single mother adolescents. The research method used is qualitative research with a descriptive approach and data collection in the form of interviews. Participants in this study were 3 single mother adolescents with the following characteristics: a) single mother adolescents, b) aged 11-21 years, c) residing in Kupang City. The data analysis technique used in this research is data analysis technique before in the field, during in the field, and after in the field using the Miles and Huberman (1984) model. The results showed that the three teenage single mothers were psychologically prosperous based on the fulfillment of six dimensions of psychological well-being, namely self-acceptance, positive relationships with others, autonomy, environmental control, life goals, and self-development.